In vivo characterization of brain metabolism by 1H MRS, 13C MRS and 18FDG PET reveals significant glucose oxidation of invasively growing glioma cells. Issue 1 (21st February 2018) - Lai, Marta; Vassallo, Irene; Lanz, Bernard; Poitry‐Yamate, Carole; Hamou, Marie‐France; Cudalbu, Cristina; Gruetter, Rolf; Hegi, Monika E.
Abstract : Glioblastoma are notorious for their highly invasive growth, diffusely infiltrating adjacent brain structures that precludes complete resection, and is a major obstacle for cure. To characterize this "invisible" tumor part, we designed a high resolution multimodal imaging approach assessing in vivo the metabolism of invasively growing glioma xenografts in the mouse brain. Animals were subjected longitudinally to magnetic resonance imaging (MRI) and 1 H spectroscopy (MRS) at ultra high field (14.1 Tesla) that allowed the measurement of 16 metabolic biomarkers to characterize the metabolic profiles. As expected, the neuronal functionality was progressively compromised as indicated by decreasing N ‐acetyl aspartate, glutamate and gamma‐aminobutyric acid and reduced neuronal TCA cycle (−58%) and neurotransmission (−50%). The dynamic metabolic changes observed, captured differences in invasive growth that was modulated by re‐expression of the tumor suppressor gene WNT inhibitory factor 1 (WIF1) in the orthotopic xenografts that attenuates invasion. At late stage mice were subjected to 13 C MRS with infusion of [1, 6‐ 13 C]glucose and 18 FDG positron emission tomography (PET) to quantify cell‐specific metabolic fluxes involved in glucose metabolism. Most interestingly, this provided the first in vivo evidence for significant glucose oxidation in glioma cells. This suggests that the infiltrative front of glioma does not undergo the glycolytic switch per se, but that environmental triggers may induce metabolic reprograming of tumor cells. Abstract : What's new? Glioblastomas are diffusely infiltrative tumors with an invasive margin that frequently lies beyond resected and irradiated areas of the brain. It is suspected that invasive glioma cells sustain diffusely infiltrative growth in microenvironments with an intact blood barrier via unique metabolic modifications. Here, using 1 H‐Magnetic resonance spectroscopy (MRS) at ultra‐high magnetic field, 16 metabolites were monitored during invasive growth of patient‐derived glioblastoma xenografts in the mouse brain. In vivo cell‐specific flux analysis by 18 FDG‐PET and 13 C‐MRS revealed significant glucose oxidation of invasively growing glioma cells, challenging the Warburg effect, according to which cancer cells rely primarily on glycolytic metabolism.